2015
DOI: 10.1017/s0266462315000069
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPING AN IPAD® APPLICATION FOR DATA COLLECTION IN A RHEUMATOLOGY RESEARCH CLINIC

Abstract: Entering data using the iPad® application makes the patient encounter slightly longer, but reduces "missing fields." It also eliminates the delay between clinic visit and data entry thus improving the efficiency of clinical data capture in a research setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Electronic and web-based PROMs are appealing in the advancing technologic era. They offer several theoretical advantages, including a simple workflow for data collection,8, 14 a greater access to pertinent patient information, and the opportunity to incorporate that data into clinical care with real-time availability of data 6, 9, 11. Furthermore, it has been reported that electronically administered PROMs yield a 14-fold probability of obtaining a completed and thus a score-able survey 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic and web-based PROMs are appealing in the advancing technologic era. They offer several theoretical advantages, including a simple workflow for data collection,8, 14 a greater access to pertinent patient information, and the opportunity to incorporate that data into clinical care with real-time availability of data 6, 9, 11. Furthermore, it has been reported that electronically administered PROMs yield a 14-fold probability of obtaining a completed and thus a score-able survey 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that electronically administered PROMs yield a 14-fold probability of obtaining a completed and thus a score-able survey 3 . The use of iPad in data collection has been shown to detect 67% of omissions seen on the pen-and-paper counterparts 6 …”
Section: Discussionmentioning
confidence: 99%
“…Practical guidance for data management addressed a variety of topics, including managing data in the field, improving management workflow, and using databases and registries to structure the data [61][62][63][64][65]. Additional guidance for practice covers using mobile technology for data collection, reusing data from electronic health records, and graphical methods to explore such data collections [66][67][68].…”
Section: Managing Study Datamentioning
confidence: 99%
“…15–17 Two additional apps operationalize the CAM-ICU assessment, the most widely used CAM identification tool in intensive care unit settings. 18 , 19 However, there are currently no apps for the UB-2 or 3D-CAM, nor one that combines the 2 as described above. To facilitate implementation of this 2-step, adaptive delirium identification protocol, we aimed to develop a portable, user-friendly, and efficient mobile application (app) embedding both the UB-2 and 3D-CAM, as part of the Researching Efficient approaches to Delirium Identification (READI) project.…”
Section: Introductionmentioning
confidence: 99%